Análisis, diseño e implementación de una herramienta WEB, en plataforma LINUX, con estándares de QoS. Para el control y monitoreo de tráfico en la Red del Área de la Energía, las Industrias y los Recursos Naturales no Renovables de la Universidad Nacional de Loja. - Guerrón Eras, Jorge Cástulo (2009)
This work takes as its main objective to design a tool that is helpful to administrators of a network, so that at the end of the interaction are the ability to improve the performance of the internet, making control at different levels are these by protocols, IP network equipment or subnets, allowing access to the tool according to user privileges, stored the information in a database, and upon completion conduct a performance analysis tool, based on standards QoS.